The Use of the Concept of Logoprophylaxis in the Process of Supporting the Development of the Subjective and Personal Existence of Children and Adolescents - Jarosz, Katarzyna (Paedagogia Christiana, 2026)
The aim of the article is to present the possibilities of using the theoretical and empirical assumptions of the concept of logoprevention in the process of supporting the development of the subjective and personal existence of children and adolescents. Logoprophylaxis, referring to the integral concept of a multidimensional human being formulated by V. E. Frankl as part of the Third Vienna School of Psychothera, enables the design and implementation of activities supporting the development of protective factors in relation to the noetic dimension of personality. They can be implemented at the level of universal, selective and indicated prevention. The strategies constructed within it (the strategy of providing existentially significant experiences and the strategy of noetic qualities) are methods of conduct consistent with the theory, on which preventive programs are based, which are ready-made tools that enrich the work of teachers and educators. They show ways of strengthening the potential of the noetic dimension of personality, which can significantly contribute to the develop ment of the subjective and personal abilities of the young generation, to manage their lives, fulfil themselves and discover the meaning of life by realising existentially significant values. It may also include the construction of new preventive programs addressed to children and adolescents.